THE LEVEL OF DIRECTNESS IN APOLOGISING IN AKEELAH AND THE BEE MOVIE DIALOGUE - Hawa, Faiza; Sukmaningrum, Rahmawati (ETERNAL, 2011)
This paper discusses precisely the production of the speech acts of apology.The choice for apology is due to its popularity as a study of speech act and being anillocutionary force so common to take place in daily context. This paper aims toexplicate the appropriate strategies of conveying apologies as part of Speech Acts inthe social interaction done by the speaker and addressee in movie conversation.Apologies is one of these speech acts, discussed through the analysis of conversation inâAkeelah and the Beeâ movie concerned with the level of directness. The data for theanalysis is taken from the dialogue transcripts of Akeelah and the bee movie. Remedialapology with assymetrical relationship are mostly found in the dialogue. The various wayof conveying apology between the characters prefers in polite apology.Keywords : Apology, politeness, the level of directness